Fly Me to the Moon : An Insider's Guide to the New Science of Space Travel - Belbruno, Edward, 1951- (Book collections on Project MUSE., 2013)
When a leaf falls on a windy day, it drifts and tumbles, tossed every which way on the breeze. This is chaos in action. In Fly Me to the Moon, Edward Belbruno shows how to harness the same principle for low-fuel space travel--or, as he puts it, ""surfing the gravitational field."" Belbruno devised one of the most exciting concepts now being used in space flight, that of swinging through the cosmos on the subtle fluctuations of the planets' gravitational pulls. His idea was met with skepticism until 1991, when he used it to get a stray Japanese satellite back on course to the Mo.